The English connection : the Puritan roots of Seventh-Day Adventist belief - Ball, B. W. (Bryan W.) (J. Clarke, 2014)
A historical study of 17th century Puritan theology, showing how many of its specific doctrines influenced the development of Seventh-Day Adventism. This book begins with a comprehensive history of Puritanism, emphasising its reliance on biblical exegesis and exposition, and the factors which contribute to collection of many strands.